Analyzing the Role of Quizizz in Integrating Language Assessment with Language Skills : A Library-Basefd Study - Muhammad Rafli; Masagus Firdaus (Pusat Riset dan Inovasi Nasional, 2025)
The integration of technology in language education has significantly influenced how teachers assess students' language skills. This library-based study explores the role of Quizizz, a gamified online assessment platform, in supporting the integration of language assessment with the four major language skills: listening, speaking, reading, and writing. Drawing on recent scholarly literature published between 2020 and 2025, the study identifies the platform’s strengths in assessing receptive skills through multimedia-supported tasks and real-time feedback. It also highlights the motivational effects of gamification, including increased learner engagement and reduced language anxiety. While Quizizz has limitations in evaluating productive skills, the findings suggest that these can be addressed through blended approaches that combine Quizizz with other digital tools. The study concludes that, when implemented creatively, Quizizz can serve as an effective formative assessment tool in modern, learner-centered language classrooms.